Influence Communication, Commitment and Integrity on Wedding Service Quality at KUA, Cibinong District, Bogor Regency - Zaelani, Abdul Qadir; Firdaus, Muhammad Azis; Walujadi, Dedi (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This Study aim For analyze influencing factors​ quality services at the Cibinong Regency Religious Affairs Office (KUA), Bogor Regency, in particular in context communication, commitment, and integrity lord in serve wedding poor society. Research methods descriptive done with 194 respondents use random sampling method. Analysis results show that communication, commitment, and integrity in a way simultaneous influential significant to quality service. Variable independent the influence as much as 57% quality service, while 27.7% is influenced by factors other. Findings This confirm importance role factors the in increase quality services at KUA.. Keywords : Quality Service, KUA, Communication, Commitment, Integrity, Poor Communities.